Quantum computing in practice with IBM Q experience : practical recipes to code real quantum computers, gates, and algorithms using IBM Qx, Qiskit and Python /: practical recipes to code real quantum computers, gates, and algorithms using IBM Qx, Qiskit and Python. (2020) - Norlen, Hassi
No abstract available